Legal Certainty on Land Ownership Rights Above Management Rights - Effendi, Alwaahab Agirda Nugraha; Setiawan, Akhmad Darajati (Universitas Negeri Semarang, 2023)
The development of legal product shows its influence with the occurrence of a tug-of-war pattern between responsive legal products and conservative legal products. The formal legal policy of Law Number 11 of 2020 concerning Job Creation (UUCK) starts from the government's political will, which is expected to be able to break the chain of bureaucracy and harmonize government policies to support the investment climate. One of the efforts is a change in legal products in agrarian affairs related to Hak Milik and Hak Pengelolaan. Hak Milik can be issued on Hak Pengelolaan land, but the nature of Hak Milik as the strongest and most complete right over the land will experience ambiguity if issued on Hak Pengelolaan land as a state-controlled right that does not result in the cancellation or release of Hak Milik. This results in a lack of legal certainty regarding the position of Hak Milik. This study examines how Government Regulation Number 18 of 2021 concerning Hak Pengelolaan, Hak Atas Tanah, Condominium Units, and Land Registration as a derivative of UUCK provides legal certainty for Hak Milik standing on Hak Pengeloaan. The results of the study show that Hak Milik, Hak Guna Bangunan and Hak Pakai issued on Hak Pengelolaan do not result in the cancellation of the legal relationship with the holder of Hak Pengelolaan. Hak Pengelolaan can be released through a mechanism of releasing rights, the process of which is reported to the Ministry of Agrarian and Spatial and then released as state land for subsequent application for the issuance of Hak Milik to eligible right applicants and Hak Pengelolaan will automatically be cancelled if Hak Milik have been issued on Hak Pengelolaan based on a letter of approval from the holder of Hak Pengelolaan